Innovation of Tri Hita Karana Yoga Model in Improving Mental Well-being of Independent Student Exchange Program Participants - I Wayan Muliarta; Ketut Chandra Adinata Kusuma; Gede Doddy Tisna; Jian Bang Deng (Yayasan Keluarga Guru Mandiri, 2024)
This study was motivated by the importance of mental well-being for students participating in independent student exchange programs, who often face challenges in social, cultural, and academic adaptation. Tri Hita Karana Yoga Model that integrates Balinese local wisdom, is believed to help overcome psychological stress and improve mental well-being. This study aims to analyze the impact of implementing the Tri Hita Karana Yoga Model on the mental well-being of students in student exchange programs. The method used was an experiment with a pretest-post-test design, involving participants who were given intervention for several weeks. Data analysis was carried out using the Paired Sample t-test to measure differences in mental well-being before and after the intervention. The results showed that there was a significant difference between the mental condition of participants before and after being given treatment, with a significant increase in the average mental well-being score. In conclusion, the Tri Hita Karana Yoga Model is effective in improving students' mental well-being. The contribution of this study to science is to expand the understanding of the benefits of yoga integrated with local wisdom in supporting mental health, as well as providing recommendations for the development of mental well-being intervention programs among students, especially in the context of academic exchange.